EXPERIENCE IN THE USE OF ATORVASTATIN IN PATIENTS WITH RHEUMATOID ARTHRITIS AND HYPERCHOLESTEROLEMIA - Komendantova, N.S.; Kulakov, Y.V.; Lukyanov, P.A.; Sinenko, A.A. (European Scientific Journal, ESJ, 2014)
In recent years there has been increased interest in the problem of reducing cardiovascular risk in patients with rheumatoid arthritis (RA). To this end it is proposed to use statins, the effects of which are now being actively studied. The purpose of this work is to determine the possibility of use of atorvastatin in patients with RA and hypercholesterolemia. The study included 42 patients with RA and moderate hypercholesterolemia and 26 practically healthy women (control). We studied lipid spectrum, DAS28, levels of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-alpha), interleukin 1Î², 10 (IL-1Î², IL-10), matrix metalloproteinase-9 (MMP-9) and its complex with tissue inhibitor-2 (MMP-9/TIMP-2). Patients with RA and moderate hypercholesterolemia in the complex therapy atorvastatin were administered at a dose of 20mg per day. We analyzed the stated figures in these patients before and after 6 weeks of treatment. In all patients with RA and moderate hypercholesterolemia on therapy with atorvastatin decreased total cholesterol (TC), low-density lipoprotein (LDL) and triglycerides (TG), indicators DAS28, ESR, CRP, concentrations of TNF-alpha, IL-1Î², IL-10, MMP-9, MMP-9/TIMP-2. These data prove lipid-reducing and anti-inflammatory effects of atorvastatin, that allows to consider the application of this drug in patients with RA hypercholesterolemia in the complex therapy to reduce cardiovascular risk.